2015
DOI: 10.1097/md.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Acute Anticholinesterase Pesticide Poisoning Caused a Long-Term Mortality Increase

Abstract: Acute anticholinesterase pesticide (organophosphate and carbamate) poisoning (ACPP) often produces severe complications, and sometimes death. We investigated the long-term mortality of patients with ACPP because it is not sufficiently understood. In this retrospective nationwide population-based cohort study, 818 patients with ACPP and 16,360 healthy comparisons from 1999 to 2010 were selected from Taiwan's National Health Insurance Research Database. They were followed until 2011. Ninety-four (11.5%) ACPP pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…A possible explanation is that the younger population has fewer comorbidities than the older population, and therefore APAP poisoning may become the major contributor to death. This finding is consistent with results of previous studies on poisoning [ 19 , 20 ]. The increased all-cause mortality was higher during the whole follow-up period and was highest in the first 12 months after APAP poisoning.…”
Section: Discussionsupporting
confidence: 94%
“…A possible explanation is that the younger population has fewer comorbidities than the older population, and therefore APAP poisoning may become the major contributor to death. This finding is consistent with results of previous studies on poisoning [ 19 , 20 ]. The increased all-cause mortality was higher during the whole follow-up period and was highest in the first 12 months after APAP poisoning.…”
Section: Discussionsupporting
confidence: 94%
“…A nationwide study reported that carbon monoxide poisoning was associated with increased long-term mortality, especially in the age subgroup of < 30 years, followed by 30–49 years [ 16 ]. This phenomenon was also found in another study, which reported that anticholinesterase poisoning increased the long-term mortality, especially in the age subgroup of < 35 years [ 17 ]. The authors concluded that the younger population has few comorbidities, and therefore, acute poisonings such as carbon monoxide and anticholinesterase pesticide poisonings may play major roles responsible for their death [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 75%
“…[ 18 ] Another study mentions a mortality rate due to poisoning with cholinesterase inhibitors (organophosphorus and carbamate) of 12.7%. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%